The dynamics of difference: oppression, cross-cultural liberation and the problems of imperialism and paternalism - Oelofsen, Marianna Christina (Rhodes University, Faculty of Humanities, Department of Philosophy, 2006)
This dissertation defends an account of oppression and supports a specific means of engaging with oppression cross-culturally. The project examines whether it is defensible to interfere in other cultures at all. Both the cultural relativist and the neo-imperialist approaches are argued to be an inadequate response to the question of whether it is defensible to interfere in other cultures, as both these approaches neglect the autonomy of the agents concerned. This project has two related goals. It first advances an answer to the question 'what is oppression?' An account of oppression is developed which will enable oppression to be identified cross-culturally. In order to start constructing an approach which will be adequate to respond to the question of interference, it is necessary to consider a means of identifying oppression crossculturally. The second objective is to examine the possibility of non-imperialistic and nonpaternalistic cross-cultural liberation projects. The first aim (advancing an account of oppression), is executed through arguing for an ethical framework which will be helpful in this context, and arguing for an account of oppression derived from this framework. The second aim (examining the possibility of non-imperialistic and non-paternalistic liberation), is carried out in two parts. The first part responds to two standard objections from cultural relativism, which would accuse a universal account such as mine of imperialism and paternalism. The first objection claims that a universalist account neglects historical and cultural difference, while the second objection claims that it neglects autonomy. In responding to these objections, it is noted that while my responses prove, theoretically, that a universal account of oppression need not lead to imperialism or paternalism, there is a danger that the account could become imperialistic and paternalistic in its application. With the intention of dealing with this problem, I advance a methodology of cross-cultural understanding which would reduce the likelihood of imperialism and paternalism in liberation projects. This notion of cross-cultural understanding is the most important contribution of this project. The objective is not to give practical judgments on when a specific liberation project is in fact paternalistic or imperialistic, but rather to propose guidelines which would need to be applied to each particular instance.
Keywords: Oppression (Psychology); Culture conflict; Multiculturalism; Political ethics; Imperialism; Paternalism